World-Systems and Globalization - Chase-Dunn, Christopher (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is a course on the historical evolution of world-systems. We will compare stateless, state-based, and modern world-systems to examine the rise and fall of large policies and the expansion and contraction of trade networks. The evolutionary history of capitalist globalization and the emergence of anti-systemic transnational movements will also be studied.Systematic comparisons are made between multisocietal systems with attention to qualitative changes in the logic of social development. General theories of social evolution and historical development will be considered. The dynamics of the rise and fall of chiefdoms, states, empires, and modern hegemons will be studied. Earlier processes of pulsation in which trade networks expanded and contracted will be compared with recent waves of global integration in the modern world-system.